Cognitive rehabilitation of neuropsychological deficits and mild cognitive impairment: A review of the literature - Miotto,Eliane Correa (2008)
Abstract Neuropsychological rehabilitation is related to the treatment or optimization of disabilities, handicaps and cognitive deficiencies including emotional, behavioral and personality alterations, aiming at the best cognitive, neurobiological and social re-adaptation. Objective: The main aim of this paper is to review scientific studies published over the last five years on cognitive training with rehabilitation, focusing on elderly subjects with cognitive complaints and patients diagnosed with MCI. Methods: Data were generated from Medline, PsychoInfo and EMBASE including publications from 2002 to 2007 using the search terms "Mild Cognitive Impairment", "Cognitive Complaints", "Rehabilitation" and "Intervention Studies". Data collection criteria were restricted to the quality of evidence Class I. Results: Eight articles out of sixty eight previously selected were chosen because of their randomized studies, including techniques of cognitive rehabilitation in patients with cognitive complaints, MCI and neuropsychological training. Conclusions: The studies showing generalization of rehabilitation techniques to practical real life situations and use of an errorless learning approach were considered more effective in terms of maintaining treatment follow up, although further studies are recommended.